The Effect of Leadership Head of Nurse on Career Development Nurse in The Hospital Inpatient Room Rsud. Dr. H. Moch Ansari Saleh Banjarmasin: Pengaruh Kepemimpinan Kepala Ruangan terhadap Pengembangan Karir Perawat di Ruang Rawat Inap Rsud Dr. H. Moch Ansari Saleh Banjarmasin - Novranty, Elssa; Basit, Mohammad; Mahmudah, Rifa’atul (LPPM STIKES Guna Bangsa, 2024)
Leadership is a process of influencing and directing group members to carry out their duties. Apart from that, leaders are expected not only to give orders to employees, but also to increase their employees' motivation to work. The leadership of the head of the room has a strong influence on the career development of nurses, where a leader or head of the room serves as a provider of instructions to his employees. The head of the room is someone who is given the authority or responsibility to organize and control nursing activities in the ward. Career development must include work performance, work motivation, commitment, discipline, and must be supported by the leader. Knowing how the influence of the head of the room's leadership on the career development of nurses in the inpatient room of RSUD. Dr. H. Moch Ansari Saleh Banjarmasin. This study uses quantitative methods with cross sectional design. The sample size was 33 respondents with total sampling technique. The data analyzed was using the spearman rank test with a value of p=0.843. The results of the bivariate analysis using the spearman rank test obtained a value of P = 0.843 which means greater than (>0.05), therefore it is stated that there is no effect of the leadership of the head of the cave. There is no influence of the head of the room's leadership on the career development of nurses in the RSUD inpatient room. Dr. H. Moch Ansari Saleh Banjarmasin.